Edukasi Kesehatan untuk Meningkatan Pengetahuan Mengenai Bahaya Rokok pada Masyarakat Wilayah Pesisir Kabupaten Konawe Utara - Nurhijrianti Akib; Hariati Lestari; Listy Handayani; Waode Mitha Fatrisya; Halik Halik; Nur Illiyyin Akib; Rifa'atul Mahmudah; Vica Aspadiah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Health education on the dangers of smoking plays an important role in increasing public awareness of the adverse health effects associated with smoking and promoting healthier lifestyles. This community service activity was conducted in Banggina Village, Motui Sub-district, North Konawe Regency, with the aim of examining the relationship between health education and changes in community smoking behavior. A quantitative approach with a quasi-experimental design was employed. The study involved 20 respondents selected through purposive sampling. The educational intervention was implemented in July 2025 and consisted of counseling sessions covering the harmful substances contained in cigarettes, the health risks of active and passive smoking, and the long-term consequences of tobacco use. Participants’ knowledge was measured using pre-test and post-test questionnaires administered before and after the educational session. The pre-test results indicated that 60% of respondents had good knowledge regarding the dangers of smoking. Following the intervention, the proportion of respondents with good knowledge increased to 95%, demonstrating a statistically significant improvement (p-value = 0.000). These findings indicate that health education is highly effective in enhancing community knowledge and awareness of smoking-related health risks. Improved knowledge is expected to encourage positive behavioral changes, reduce smoking habits, and support the adoption of healthier lifestyles. Continuous and community-based health education programs are recommended to sustain these positive outcomes and strengthen smoking prevention efforts at the community level